2019
DOI: 10.3390/microorganisms7120624
|View full text |Cite
|
Sign up to set email alerts
|

Environmental DNA Sequencing Reveals a Highly Complex Eukaryote Community in Sansha Yongle Blue Hole, Xisha, South China Sea

Abstract: We report an Illumina high-throughput sequencing protocol of eukaryotic microbes in the world’s deepest marine blue hole, Sansha Yongle Blue Hole, Xisha, South China Sea. The variable V9 region of small subunit (SSU) rDNA, was sequenced using this approach from the waters of blue hole and outer reef slope. 917,771 unique eukaryotic 18S rRNA gene sequences and 6093 operational taxonomic units (OTUs) were identified. Significant differences in the eukaryotic composition were observed between the blue hole and ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 41 publications
0
14
0
Order By: Relevance
“…Most anchialine cave studies documented endemism among eukaryotes [12]. Relatively few studies have attempted to record the full diversity of microbial communities in anchialine ecosystems [13][14][15], even though these studies resulted in descriptions of new species using novel molecular tools. In the region of the eastern Adriatic Sea, the majority of anchialine ecological studies have been based on the taxonomic research of stygobiotic metazoans [16], the distribution of trace metals [17], and iodine species and nutrients [18].…”
Section: Introductionmentioning
confidence: 99%
“…Most anchialine cave studies documented endemism among eukaryotes [12]. Relatively few studies have attempted to record the full diversity of microbial communities in anchialine ecosystems [13][14][15], even though these studies resulted in descriptions of new species using novel molecular tools. In the region of the eastern Adriatic Sea, the majority of anchialine ecological studies have been based on the taxonomic research of stygobiotic metazoans [16], the distribution of trace metals [17], and iodine species and nutrients [18].…”
Section: Introductionmentioning
confidence: 99%
“…Depth partitioning of plankton microbiome in the SYBH Environmental heterogeneity is regarded as a universal driver of biodiversity (Stein et al, 2014), thus the strong vertically heterogeneous environment in the SYBH explained its higher plankton diversity than that in outer reef slope and other Chinese marginal seas (He et al, 2019;Liu et al, 2019;Li et al, 2020b). In this study, our joint analysis of microeukaryotic and prokaryotic plankton found that planktonic microbiome above 150 m in the SYBH was vertically structured along the abiotic gradients and grouped into three clusters as upper oxic layer (0-20 m), middle oxic layer (40-80 m) and suboxic-anoxic layer (90-150 m) (Figures 1D, 3).…”
Section: Discussionmentioning
confidence: 99%
“…In aquatic ecosystems, plankton serve as one of the sensitive indicators of biodiversity and environmental changes, and underpin important ecosystem functions (e.g., Ibarbalz et al, 2019;Sunagawa et al, 2020), thus scientists have started to explore the community composition of plankton and its relationship with environmental variables in SYBH. Prokaryotic plankton including bacteria and archaea community (He et al, 2019;Zhang et al, 2021), microeukaryotic plankton (Liu et al, 2019), microphytoplankton (Ge et al, 2020) and mesozooplankton (Chen et al, 2018) in SYBH have been investigated separately, with some lineages such as a genus of gram-negative bacteria Vibrio (Li et al, 2020a) and foraminifera (Li et al, 2020b) being addressed. However, the assembly mechanism of plankton microbiome, the role of subcommunities of different abundance and the potential microbial biointeraction remain elusive, which is crucial for understanding the ecological processes in SYBH.…”
Section: Introductionmentioning
confidence: 99%
“…This, for several reasons, some, fundamental and related with the search for the limits of life [ 2 ], and others, more pragmatic and focused on the biotechnological potential of extremophiles, has sparked a marked growth of interest in the ecology of extreme environments [ 3 ]. The 2019–2020 version of Extremofiles 2.0, a Special Issue of Microorganisms devoted to extremophiles, has gathered eleven papers dealing with different aspects of microorganisms that thrive in extreme environments: five on halophiles [ 4 , 5 , 6 , 7 , 8 ], three on acidophiles [ 9 , 10 , 11 ], one on thermophiles [ 12 ], one on psycrophiles [ 13 ] and one on metal resistant microorganisms [ 14 ].…”
mentioning
confidence: 99%
“…Liu et al analyzed the complex eukaryotic community in the world’s deepest marine blue hole in the South China Sea, where significant differences were observed at different depths, and the most abundant microalgae assemblages detected were Dinophyceae at 10–20 m water column [ 4 ].…”
mentioning
confidence: 99%